Legal analysis of disparity in military court judges' decisions faced with the principle of military interests - Galih Wahyu Sasmito (Annals of Justice and Humanity, 2024)
Purpose: The focus of the discussion in this study is the decision on crimes against morality committed by TNI soldiers. Research methodology: The research method used is normative juridical which is carried out by analyzing various decisions related to crimes against morality committed by TNI soldiers and related laws and regulations. Results: The verdict of the military court in cases of criminal acts of indecency committed by the TNI which were sentenced to prison sentences were relatively the same, ranging from five months to one year, but for additional penalties in the form of dismissal from the TNI service there was a disparity of 34% which caused legal uncertainty for every TNI soldier who committed a criminal act of indecency, especially with the penalty of dismissal from the TNI Service. The influencing factor on the judge's decision for additional criminal dismissal is related to military interests which state that the perpetrators of criminal acts of indecency are still needed by the TNI Institution and have an important role in supporting the main tasks of the TNI and there is no replacement who has the same ability as the perpetrators of criminal acts of indecency so that the judge's decision does not include the additional penalty of dismissal from the TNI service.